Designing a safe and sustainable pediatric neurosurgical practice: the English experience. Issue 7 (July 2014) - Young, Amber E.; Soriano, Sulpicio
Summary The 2001 Report of the Public Inquiry into children's heart surgery at the Bristol Royal Infirmary 1984–1995 stated that there must be standards for hospitals as a whole and that hospitals, which do not meet these standards, should not be able to offer services within the National Health Service (NHS). In 2013, agreed standards for pediatric neurosurgery were produced. Between 2001 and 2013 several key documents were published, which formed the background to the review that produced these standards:, the 'Safe and Sustainable' review. The process had the mission statement, 'Safe, sustainable and world class. Not ordinary, OK or just good enough.' In April 2013, the new commissioning structure of NHS England came into being. Clinical Reference Groups (reporting directly into the new structure) and pediatric neurosurgical operational delivery networks are taking the Safe and Sustainable pediatric neurosurgery standards and models of care into practice in England. Effective outcome data collection will allow us to assess whether these networks will improve equity of access for English children to world‐class pediatric neurosurgical care and reduce the variation in outcomes seen at the present time.